Noninvasive assessment for acute allograft rejection in a rat lung transplantation model. Issue 12 (18th December 2014) - Takahashi, Ayuko; Hamakawa, Hiroshi; Sakai, Hiroaki; Zhao, Xiangdong; Chen, Fengshi; Fujinaga, Takuji; Shoji, Tsuyoshi; Bando, Toru; Wada, Hiromi; Date, Hiroshi
Abstract After lung transplantation, early detection of acute allograft rejection is important not only for timely and optimal treatment, but also for the prediction of chronic rejection which is a major cause of late death. Many biological and immunological approaches have been developed to detect acute rejection; however, it is not well known whether lung mechanics correlate with disease severity, especially with pathological rejection grade. In this study, we examined the relationship between lung mechanics and rejection grade development in a rat acute rejection model using the forced oscillation technique, which provides noninvasive assessment of lung function. To this end, we assessed lung resistance and elastance (RL and EL) from implanted left lung of these animals. The perivascular/interstitial component of rejection severity grade (A‐grade) was also quantified from histological images using tissue fraction (TF; tissue + cell infiltration area/total area). We found that TF, RL, and EL increased according to A‐grade. There was a strong positive correlation between EL at the lowest frequency (Elow; EL at 0.5 Hz) and TF (r2 = 0.930). Furthermore, the absolute difference between maximum value of EL (Emax) and Elow (Ehet; Emax − Elow) showed the strong relationship with standard deviation of TF (r2 = 0.709), and A‐grade (Spearman's correlation coefficients; rs = 0.964, P < 0.0001). Our results suggest that the dynamic elastance as well as its frequency dependence have the ability to predict A‐grade. These indexes should prove useful for noninvasive detection and monitoring the progression of disease in acute rejection.